Provisional Agenda for the Thirtieth Meeting of the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2014)
The following is the provisional agenda for the Thirtieth Meeting of the International Monetary and Financial Committee, which is to be convened at the IMF's Headquarters in Washington, D.C. on October 11, 2014.